The Report of the Study Team on Centre-State Relationships Volume III - Planning Commission (Planning Commission, 1975)
The Education Secretary to the Government of India is the Chairman of the Organization and its members include senior officers of the Ministries of Home Affairs, Defence, Works, Housing and Supply and Finance, as well as distinguished Educationists, including representatives of the Central Board of Secondary Education, the National Council of Educational Research and Training and state governments.
The Report of the Study Team
Submitted to the Administrative Reforms Commission
Keywords: Shall Scale Industries; minor Irrigation; national cooperative; Development corporation; Animal Husbandry Including dairying; Agricultural marketing; Social Welfare; School Education